2018
DOI: 10.1080/13552600.2018.1476600
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ level of knowledge of and supportive attitudes to sexual crime in the Swedish context

Abstract: The aim of the present study was twofold. First, we wanted to quantify the level of knowledge of Swedish young people regarding sexual crime and to evaluate their supportive attitudes, while at the same time we aimed at identifying, through self-report, the sources that most contribute to such knowledge and attitudes. A sample of 245 upper secondary school students was selected from five schools in four Swedish counties. The results indicate that adolescents in Sweden have a high level of knowledge of rape, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
0
5
0
1
Order By: Relevance
“…Usia mempengaruhi proses berfikir seorang remaja, semakin tua usia seseorang maka pengetahuan yang diperoleh semakin meningkat. Remaja dengan keturunan Eropa memiliki pengetahuan lebih baik dibandingkan dengan latar belakang etnis lain (Svensson et al, 2019). Kelompok etnis yang berbeda dalam nilai-nilai seksual mereka dikarenakan adanya pengaruh budaya, politik dan agama yang beragam pada dukungan norma, peran gender dan berakibat pada seksualitas (Safdar & Kosakowska-Berezecka, 2015).…”
Section: Pembahasan 1 Jenis Pelecehan Seksualunclassified
“…Usia mempengaruhi proses berfikir seorang remaja, semakin tua usia seseorang maka pengetahuan yang diperoleh semakin meningkat. Remaja dengan keturunan Eropa memiliki pengetahuan lebih baik dibandingkan dengan latar belakang etnis lain (Svensson et al, 2019). Kelompok etnis yang berbeda dalam nilai-nilai seksual mereka dikarenakan adanya pengaruh budaya, politik dan agama yang beragam pada dukungan norma, peran gender dan berakibat pada seksualitas (Safdar & Kosakowska-Berezecka, 2015).…”
Section: Pembahasan 1 Jenis Pelecehan Seksualunclassified
“…However, the researchers did not focus on the relationship of all variables with media exposure. Svensson, et al (2018) had indicated the relationship of knowledge about sexual harassments and attitude towards sexual harassments. The authors had explored that good knowledge of sexual harassments can develop an intolerant attitude towards sexual harassments.…”
Section: Studies On the Relation Among Propensity To Act Against Sexual Harassments (Behavior) Sexualmentioning
confidence: 99%
“…One of the biggest problems with violence against adolescents is that the number of report-based incidents is small, and of these, only a small proportion can be validated by law enforcement [ 9 ]. The low reporting rate may be related to the reluctance to report, limited knowledge, and different perspectives on violence [ 10 , 11 ]. The data obtained are usually based on official reports from government ministries/agencies, cases reported to law enforcement agencies, patients admitted to hospitals, or data from non-government organisations.…”
Section: Introductionmentioning
confidence: 99%
“…Data from the police and judicial system have long been considered the most reliable; however, figures depend heavily on people being willing to report incidents. Several studies have pointed out a significant difference between police data and hospital emergency data [ 9 , 10 ]. From a forensic angle, the low success rate of legal prosecution may be due to underreporting and weak case handling [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%